The indigenous uses of plants from Siberut, Mentawai, Indonesia - Lee, Samantha; Nichols, J Doland; Lloyd, David; Sagari, Santi; Sagulu, Filemon; Siregar, Iskandar Z; Hartoyo, Adisti Permatasari Putri; Henry, Rob; Nurainas, Nurainas (Ethnobotany Research and Applications, 2021)
Background: Indigenous knowledge systems, like those traditionally practiced by the Mentawai people from the Mentawai Islands, West Sumatra, Indonesia, are a deep-time laboratory that examines how people manage or failed to find adaptive solutions to changes in their surroundings, including biodiversity loss and changing climate. However, many of these practices, including Mentawai’s traditional knowledge system, arat sabulungan, are eroding. Given that Indigenous knowledge systems are believed to make up at least half of humanity’s intellectual heritage, adequate documentation of traditional ecological knowledge is needed, as too are appropriate systems that support the perpetuation of such knowledge. This paper identifies the indigenous uses of Siberut’s flora and explores how this knowledge may underlie the conservation of Siberut’s unique biodiversity. Mentawai values and attitudes toward their traditional ecological knowledge and reasons why their traditional knowledge is eroding are also examined. Methods: Primary data was derived from various sources, including: observation of peoples’ day-to-day activities; community surveys (number of participants = 494) and key informant interviews (number of informants = 21); and plant collection and identification. Research participants in the community survey were chosen based on their interest and willingness to partake in the survey. Key informants were chosen based on their reputation within the community on the extent of their plant knowledge. Results: Ethnobotanical data suggests that the Mentawai have ethnobotanical uses for at least half of all plant species on record. Though 98 percent of respondents felt their traditional knowledge is important for the future of Mentawai, a majority felt there were substantial threats to the continuation of their traditions. Conclusion: Data gathered during the research period suggests that Mentawai indigenous practices and traditions play a critical role in conserving Siberut’s unique biodiversity.